Effect of pulsed electric current treatment on corrosion of structural metals - Babutskii, A.I.; Chrysanthou, A.; Ioannou, J. (Проблемы прочности, 2009)
Results of corrosion tests of some structure metals
previously treated using pulsed electric current
of high density are presented. According to
the data obtained, the treatment substantially affects
corrosion of metals. In cases of HSLA steel
and 5182 aluminum alloy, an increase of corrosion
resistance occurs, whereas the same treatment
causes a dramatic reduction of corrosion
resistance of 5754 aluminum alloy. Наведено результати випробувань на корозію ряду конструкційних матеріалів,
що попередньо зазнавали впливу імпульсного електричного струму
високої густини. Установлено, що така обробка суттєво впливає на корозію
матеріалів. Для сталі HSLA й алюмінієвого сплаву 5182 має місце зростання
опору корозії, в той час як для алюмінієвого сплаву 5754 - різке зменшення
опору корозії. Представлены результаты испытаний на коррозию ряда конструкционных материалов, предварительно
подвергаемых воздействию импульсного электрического тока высокой плотности.
Установлено, что такая обработка существенно влияет на коррозию исследуемых
материалов. Для стали HSLA и алюминиевого сплава 5182 происходит рост сопротивления
коррозии, в то время как для алюминиевого сплава 5754 - резкое уменьшение сопротивления
коррозии.